An Improved Approach for Measuring Cracking and Decompression Moments in Prestressed Concrete Members. Issue 1 (2nd January 2018) - Guo, Wen-long; Han, Zhi-jiang; Chen, Y. Frank; Liu, Zhi-hua; Ni, Ying-sheng
Abstract: A relatively new experimental-analytical method for determining the location separating the cracking and decompression moments of a prestressed concrete (PC) flexural member is proposed. This method is based on the changeable mechanism of tension-zone reinforcement considering the variation of tensionreinforcement strain rates and the sensitivity of system parameters. The proposed method is shown to improve the sensitivity of experimental parameters on the flexural behaviour of PC members under different loading conditions. For uncracked sections, the proposed method can determine the cracking moment accurately, similarly to the traditional moment-strain curve method. For cracked sections, the traditional method cannot clearly define the transition point on the moment capacity curve as it does not separate the linear variation (before cracking) from the non-linear variation (after cracking), especially when the non-linear part is only a small portion of the total strain and varies slowly. However, the proposed method can well describe the stress change of tensile reinforcement and monitor the decompression moment at a cracked section. The proposed approach is recommended for clearer mechanical concepts, improved fundamental theory and testing convenience.